Optimization of TD-LTE shadow neighbor cells based on big data of road test - Zhechao ZHANG; Keke CHEN; Maojian LUO (Dianxin kexue)
CSFB has been adopted by many terminal manufacturers as one of the LTE voice solution. Restricted by CSFB mechanism，there exists one kind of GSM neighbor cell which is referred as shadow neighbor cell. Even without neighbor relations configured，shadow neighbor could lead UE（user equipment）to fall back successfully due to itsultra-long coverage and strong Rx level，and that would probably causes problems like dropped calls. Based on large data of road test and network of China Mobile Hangzhou Branch，the existence of shadow neighbor cell was pointed out，an optimization method of TD-LTE shadow neighbor cell was proposed，the hidden shadow neighbor cells were dug out，and they were eliminated by adjustments of antenna and frequency. Experimental results show that the method proposedis practical，effective and also worthy promotion.